Formaldehyde activation of mitoxantrone yields CpG and CpA specific DNA adducts - Parker, Belinda S. (Oxford University Press, 2000)
Recently we have found that mitoxantrone, like Adriamycin, can be activated by formaldehyde and subsequently form adducts which stabilise double-stranded DNA in vitro. This activation by formaldehyde may be biologically relevant since formaldehyde levels are elevated in those tumours in which mitoxantrone is most cytotoxic. In vitro transcription analysis revealed that these adducts block the progression of RNA polymerase during transcription and cause truncated RNA transcripts. There was an absolute requirement for both mitoxantrone and formaldehyde in transcriptional blockage formation and the activated complex was found to exhibit site specificity, with blockage occurring prior to CpG and CpA sites in the DNA (non-template strand). The stability of the adduct at 37°C was site dependent. The half-lives ranged from 45 min to ~5 h and this was dependent on both the central 2 bp blockage site as well as flanking sequences. The CpG specificity of mitoxantrone adduct sites was also confirmed independently by a λ exonuclease digestion assay.